Herramientas interactivas en la asignatura educación para la salud - Tenorio Gómez, Mario Eduardo (2022)
The research that follows was developed with the intention of knowing the use of interactive tools, by teachers, in the subject of health education. To achieve this, universal literature was reviewed on the subject of interactive tools in education in general, both their advantages and disadvantages. Additionally, we proceeded to study the impact of the tools on the health education subject itself, as well as the importance of said subject for teachers. Due to the qualitative nature of the topic, in-depth interviews were conducted with teachers of this subject to understand a little better the use of the tools in practice. The results showed that the use of interactive tools in health education is very low, mainly because teachers do not know how to use these tools or do not know how to do them at the right time. The conclusion reached is that it is necessary for educational institutions to motivate their teachers to be trained in the use of these tools to improve the experiences of students in the classroom.